Bacteriophage-resistant and bacteriophage-sensitive bacteria in a chemostat - Zhun Han; Hal L. Smith (Mathematical Biosciences and Engineering)
In this paper a mathematical model of the population dynamics of a bacteriophage-sensitive and a bacteriophage-resistant bacteria in a chemostat where the resistant bacteria is an inferior competitor for nutrient is studied. The focus of the study is on persistence and extinction of bacterial strains and bacteriophage.